1995
DOI: 10.1016/0895-7061(95)00055-t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the hemodynamic and metabolic effects of low-dose hydrochlorothiazide and lisinopril treatment in obese patients with high blood pressure

Abstract: Patients with high blood pressure tend to be insulin resistant, glucose intolerant, hyperinsulinemic, and dyslipidemic. Since these metabolic defects are accentuated by obesity, we thought it important to compare the effects of 3 months' treatment with either lisinopril (20 mg/day) or low dose hydrochlorothiazide (12.5 mg/day) on blood pressure and glucose, insulin, and lipoprotein metabolism in obese patients with hypertension. There were 14 patients in each group, and they were similar (mean +/- SE) in age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 23 publications
3
18
0
3
Order By: Relevance
“…In patients on thiazides, hypokalemia has been associated with higher FBG that improved after replacement of potassium [54]. Thiazide diuretics may impair glucose metabolism by decreasing peripheral insulin sensitivity, resulting in increasing insulin secretion [55][56][57]. Our results suggest that the probability of developing new diabetes after thiazide initiation is associated with increasing BMI [48].…”
Section: Thiazide Diureticssupporting
confidence: 53%
“…In patients on thiazides, hypokalemia has been associated with higher FBG that improved after replacement of potassium [54]. Thiazide diuretics may impair glucose metabolism by decreasing peripheral insulin sensitivity, resulting in increasing insulin secretion [55][56][57]. Our results suggest that the probability of developing new diabetes after thiazide initiation is associated with increasing BMI [48].…”
Section: Thiazide Diureticssupporting
confidence: 53%
“…However, many studies have shown that ACE inhibition has no beneficial effects on insulin sensitivity and the development of diabetes (Table 1) [15][16][17][18][19][20][21][22][23][24]. Unfortunately, several investigations on this issue are based on uncontrolled study designs and surrogate markers of insulin sensitivity, and are potentially confounded by the use of additional medication.…”
Section: Introductionmentioning
confidence: 99%
“…Most data from the literature indicate that diuretics and beta-blockers reduce insulin sensitivity and increase lipid levels (11,12); calcium channel blockers (CCB) are generally considered to be metabolically neutral (13), although some studies have indicated a positive impact on insulin sensitivity (14,15) (11,12,(16)(17)(18) …”
Section: Introductionmentioning
confidence: 99%